Retratos da vida danificada: contexto, cultura: e cotidiano na trajetória escolar de pessoas com deficiência - Miguel, Carolina Mariane (2022)
This research is about inclusive education. The more general question that arises is: in what aspects is it necessary to advance towards a inclusive education, when there is still a stereotyped culture permeated by old prejudices, even in a context of decades of scientific advance in relation to educational, health conceptions and public policies, in a daily life marked by regressive practices of invisibility for people with disabilities? Based on this question, we defined the focus of research on educational policies, from the point of view of legislation, norms and official documents, asking under which conceptions they have been limited? And, also based on the identification of advances in public policies, in financing and in the qualification of professionals, what are the questions that still pose a challenge for education to be, in fact, inclusive and emancipatory? The main hypothesis to answer this set of questions is that, although there have been important advances in the last decades, there is a cultural prevalence of stereotypes and prejudices that maintain stigmas about people with disabilities, making it difficult to effectively include them in school and in society. The general objective is to understand how the inclusion of people with disabilities in regular education has taken place, based on public educational policies that advance or remain regressed, in Brazil, especially in the last 25 years, taking into account the contexts, the cultures and the daily lives of these people. The specific objectives are: 1. Identify the current legislation that defines the schooling of people with disabilities in an inclusive perspective; 2. analyze how educational policies impact the lives of people with disabilities, especially the population with multiple vulnerabilities, in the light of Frankfurt's Critical Theory; 3. Identify what advances and what remains regressed in the reality of social practices, towards an emancipatory and inclusive education. Using negative dialectics as a method of analysis, the empirical research involves the researcher's narrative about the school trajectories of 12 people with disabilities, of different ages, portraying lives damaged by the insufficiency of public policies or by the difficulty of accessing existing policies. The study reveals that even public policies of a progressive nature, which have been advancing in the last two decades, from the perspective of inclusive education, are based on a neoliberal capitalist society, which makes invisible and objectifies people who do not adapt to the dictates of the marketplace. It also reveals that, under the recent aegis of conservative governments, on the extreme right, the segregating discourse of specialized institutions and special classes is gaining strength again, aspects that make the advances achieved regress. Considering that the main concern of the school should be the promotion of a humanized and emancipatory education, the person with disabilities puts the school in front of questions that it needs to face, in its deepest bases, with regard to inclusion and in favor of overcoming the excluding barbarism of the current model of society.